STRATEGI PEMURIDAN GENERATIF UNTUK PENDEWASAAN UMAT DAN PERTUMBUHAN GEREJA: HERMENEUTIK EFESUS 4:11 - 13 - Ronal, Ronal; Mukti, Guntur Hari; Chandra, Tjahjadi (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2025)
The growth of a healthy and sustainable church is largely determined by the effectiveness of its discipleship strategy. However, many local churches in Indonesia continue to face challenges such as ministry stagnation and low congregational engagement due to the absence of a model that encourages the active reproduction of disciples. This study aims to analyze a generative discipleship strategy based on Ephesians 4:11–13 as its theological foundation. The research employs a biblical textual study method, which combines exegetical analysis of the original meaning of the text within the context of the early church and hermeneutical interpretation for its application to the contemporary church. A literature review of primary and secondary theological sources supports the analysis in formulating a contextual and applicable discipleship model. The findings reveal that generative discipleship—which emphasizes multiplying disciples through training, mentoring, and commissioning—aligns with the fivefold ministry structure outlined in Ephesians 4 and is relevant in addressing current church needs. This strategy is effectively implemented through small groups, leadership training, and family- and community-based discipleship. In conclusion, generative discipleship serves as a vital catalyst for dynamic and transformative church growth. The study highlights the urgent need for churches to develop intentional and measurable discipleship systems, enabling each believer to function as an active disciple-maker in advancing the body of Christ.